2008
DOI: 10.1089/gte.2008.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclosporin A and Tacrolimus on Sister Chromatid Exchange Frequency in Renal Transplant Patients

Abstract: Long-term use of Cyclosporin A (CsA) and Tacrolimus is known to yield serious untoward side effects including nephrotoxicity, neurotoxicity, and malignant tumor formation. Sister chromatid exchange (SCE) is used to assess the genotoxic potential of various agents. A total of 37 postrenal transplant patients receiving either CsA (n = 20) or Tacrolimus (n = 17) were included in this study. The genotoxic effects of CsA and Tacrolimus were assessed by determination of SCE frequency. In patients receiving CsA, SCE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Absence of mutagenicity was also observed in vitro using Salmonella typhimurium (Matter et al, 1982) while mutagenicity was observed in human lymphocytes cultures treated with concentrations between 200 and 400 ng/ml of CsA (Oliveira et al, 2004). Lymphocytes of twenty post-renal transplant patients in culture demonstrated that CsA (plasma level 193.2 ± 67.5 ng/ml) increased the sister chromatid exchange (Oztürk et al, 2008). In the present study, it was demonstrated that CsA was mutagenic (MN test) in MRC-5 cells only at higher concentration evaluated (1520 ng/ml).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Absence of mutagenicity was also observed in vitro using Salmonella typhimurium (Matter et al, 1982) while mutagenicity was observed in human lymphocytes cultures treated with concentrations between 200 and 400 ng/ml of CsA (Oliveira et al, 2004). Lymphocytes of twenty post-renal transplant patients in culture demonstrated that CsA (plasma level 193.2 ± 67.5 ng/ml) increased the sister chromatid exchange (Oztürk et al, 2008). In the present study, it was demonstrated that CsA was mutagenic (MN test) in MRC-5 cells only at higher concentration evaluated (1520 ng/ml).…”
Section: Discussionsupporting
confidence: 50%
“…However, MRC-5 cells seems to be less sensitive to FK-506 since in our study mutagenic effects were observed only in concentrations higher than 24 ng/ml. Besides, Oztürk et al (2008) also did not observe an increase in sister chromatid exchange in seventeen patients treated with FK-506 (plasma level 15.2 ± 0.81 ng/ml). These different results in distinctive cell types, reinforce the need to evaluate the mutagenic effect of these drugs in other cell types besides lymphocytes.…”
Section: Discussionmentioning
confidence: 74%
“…For example, in a study, it has been reported that tacrolimus did not induce CA in Chinese hamster bone marrow cells [18], but in another study SCE frequencies were increased after cyclosporine A (CyA), which has been similar immu nosuppression mechanism with tacrolimus, treatment in kidney transplant patients [19,28]. Similarly, in another study, CyA [29] and tacrolimus [19] have been shown to not reduce genotoxic damage in postrenal transplant patients. SCE refers to the interchange of DNA between replication products, Increased SCE frequency may be indicative of the genotoxic effect of a mutagenic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that chromo somal aberrations positively correlate with cancer risk [17]. In mutagenity studies of tacrolimus did not show any genotoxic potential when tested in different sys tems [e.g., CA in Chinese hamster bone marrow cells [18], SCE in in postrenal transplant patients [19] and MN in mice or Chinese hamster [18], whereas lym phocyte cultures treated in vitro with different tacroli mus concentrations showed an increase of SCE [18]. Most of the research associated immunosuppressants has focused on the immune response or cytostatic and mutagenic effect in patients at in vivo conditions.…”
mentioning
confidence: 99%
“…The method of SCEs has been proposed as a very sensitive, simple, and rapid method for detecting mutagens and=or carcinogens, antimutagenic agents, and monitoring genetic diseases that are characterized by chromosome instability, while its application is very useful for monitoring and improving chemotherapeutic techniques in vitro and in vivo. Further, the other two indices, PRI and MI, are useful indicators of the cytostatic and cytotoxic properties of various agents (Carrano and Natarajan, 1988;Das, 1988;Lialiaris et al, 2007;Ö ztü rk et al, 2008;Papachristou et al, 2008;Karapidaki et al, 2009aKarapidaki et al, , 2009b. Elevated SCEs were found in ESRD patients compared with the healthy donors (Pernice et al, 2006).…”
Section: Introductionmentioning
confidence: 99%